The relationship between internet use preference and loneliness among college students during COVID-19: The chain mediating effect of online social support and self-esteem - Luo, Qing; Huang, Lu; Wu, Na (Frontiers in Psychology, 2022)
The outbreak of COVID-19, especially the demands of social interaction and spatial distancing behavior, has led to a surge in Internet use, which has also led to an increase in loneliness. Therefore, we investigated the role of online social support and self-esteem in the relationship between Internet use preference and loneliness. In this study, 1053 college students were surveyed with a questionnaire based on the framework of Ecological System Theory, and a chain mediation model was established to clarify the mechanism between Internet use preference and loneliness. The results show that Internet use preference not only positively predicts loneliness, but also indirectly influences loneliness through the mediators of online social support and self-esteem, thereby impacting loneliness through the “online social support → self-esteem” chain. The results also indicate the need to pay attention to college students’ mental health status during COVID-19. The advent of COVID-19 has impacted people’s lifestyles and has changed the impact of the Internet on individual mental health. This study provides a new way to further understand college students’ Internet use preferences, online social support, self-esteem, and loneliness status during COVID-19. It provides targeted interventions for college students’ loneliness during COVID-19.